Local Interaction in Tax Evasion - Barnabás M. Garay; András Simonovits; János Tóth (Hungarian Academy of Sciences, Institute of Economics, 2011)
We study a model of tax evasion, where a flat-rate tax only finances the provision of public goods. Deciding on reported income, each individual takes into account that the less he reports, the higher is his private consumption but the lower is his moral satisfaction. The latter depends on his own current report and average previous reports of his neighbors. Under quite general assumptions, the steady state reported income is symmetric and the process converges to the steady state.
Keywords: C62; H26; 330; tax evasion; steady state; asymptotic stability; symmetrization; networks; monotone maps; Steuervermeidung; Modellierung